Centralizing Trends and Pollution Law Enforcement in China. (10th August 2017) - van Rooij, Benjamin; Zhu, Qiaoqiao; Na, Li; Qiliang, Wang
Abstract: This article analyses centralizing trends that may be able to reduce the negative influence of local protectionism on environmental law enforcement in China. The article finds that as centralizing trends unfolded, enforcement over time has become stricter and more frequent, however with only minor effects in reducing pollution. Moreover it finds a situation of uneven enforcement with richer and more urbanized areas having much stronger and more frequent enforcement than inland areas. Centralizing trends may thus have spurred stronger enforcement, but concurrently allowed for an uneven enforcement. At the same time, the article finds a continued local influence, keeping enforcement too weak to have much effect in reducing pollution and allowing for local interests to shape enforcement into unequal outcomes. 摘要: 文章旨在分析中央集权化的趋势是否有可能减少地方保护主义对于中国环境执法所产生的负面影响。研究发现, 随着中央集权化趋势所呈现出来的执法实践正变得更加严格和频繁, 但是对于减少污染所起到的作用甚微。此外, 研究发现, 执法存在不均衡的情形, 即相对于内陆地区, 较富裕、城市化程度较高的地区执法强度更高、更频繁。因此, 中央集权化的趋势有可能刺激出较强的执法, 但同时也可能催生出不均衡的执法实践。与此同时, 研究发现, 地方性的影响仍然持续存在, 使得执法太弱而无法对减少污染产生显著作用, 并且使得地方性的利益塑造出不同等的执法后果。